In Vitro Inhibition of Biofilm Formation and Phytochemical Analysis of Fractions of Jatropha tanjorensis against Clinical Bacterial Pathogens - Otu Joseph; Ekpiken Solomon; Omang Donald; Adie Francisca; Agbiji Nneka; Odey Benedict; Atuo Michael (African Journal of Sciences and Traditional Medicine, 2026)
The widespread use of antibiotics has driven the emergence of resistant bacteria, leading to longer treatments, higher costs, and increased mortality in humans. This study examined the antibacterial and antibiofilm activities of Jatropha tanjorensis leaf fractions and identified the major bioactive compounds responsible for these effects. The leaves were extracted using solvents of different polarities—n-hexane, dichloromethane (DCM), ethyl acetate, and water—and each fraction was tested against selected clinical bacterial isolates. Phytochemical screening of fractions was conducted following standard procedures. GC–MS analysis was carried out to confirm and quantify phytoconstituents in the fractions. Antibacterial activity of the fractions was evaluated using agar well diffusion methods. The antibiofilm effect of the fractions was determined by a slightly modified crystal violet microtiter plate assay. Extraction yields varied, with the n-hexane fraction giving the highest recovery (70.51%) and the aqueous fraction the lowest (63.71%). Phytochemical screening revealed the presence of flavonoids, saponins, tannins, steroids, and terpenoids, while GC–MS analysis confirmed compounds such as n-hexadecanoic acid, phytol, 9-octadecanamide, and benzenedicarboxylic acid in different concentrations across fractions. These compounds are known for their antimicrobial and antioxidant properties. All fractions showed varying degrees of antibacterial activity, but the n-hexane and ethyl acetate fractions were the most effective. The ethyl acetate fraction recorded the lowest minimum inhibitory and bactericidal concentrations (12.5 and 25 mg/mL, respectively) against Escherichia coli and Proteus mirabilis. Antibiofilm assays demonstrated concentration-dependent inhibition, with the n-hexane fraction exhibiting the strongest activity (0.014 OD against E. coli). In essence, the results indicate that J. tanjorensis is rich in biologically active compounds capable of inhibiting bacterial growth and biofilm formation. These findings provide scientific support for its traditional use in managing infections and highlight its potential as a natural source for developing new antibacterial and antibiofilm agents.